P26 Hepatocellular carcinoma surveillance in patients with established cirrhosis: the Birmingham experience. (16th November 2010) - Bridgestock, H; Desai, R; Neuberger, J
Abstract : Introduction: HCC causes approximately 1500 deaths per year in the UK and 95% of patients these have known established cirrhosis. Surveillance programme for patients with cirrhosis using six monthly α-fetoprotein (AFP) monitoring and ultrasound scanning (USS) is therefore recommended to ensure early identification of HCC at a stage when curative treatment is still possible. HCC identified by surveillance rather than incidental or symptomatic diagnosis results in better outcome and increased survival. Aim: Here we show the results of an audit of HCC surveillance at the Liver Transplantation Unit in Queen Elizabeth Hospital Birmingham against the British Society of Gastroenterology guidelines. Method: We identified consecutive 271 patients who had undergone HCC surveillance between January 2007 and January 2009. We divided the patients into high risk (hepatitis B, hepatitis C, men with alcoholic liver disease or PBC and haemochromatosis) and low risk groups. We collected their demographic data, surveillance results, treatment details and outcome. Results: Mean duration of follow-up was 22 months (range 1 to 32). 156/272 (57%) patients belonged to high risk group. Ten patients (4%) ceased surveillance as they underwent liver transplantation with indication other than HCC. Eight patients (3%) died during surveillance, unrelated to HCC and one patient was found to have pancreatic carcinoma on ultrasound done for HCC surveillance. 18 (6%) were found to have HCC, of whom (72%) were in the high risk group. Number of HCC present varied from 1 (72%), 2 (22%) and 3 HCC in just 1 (6%). Two patients (11%) were detected by abnormal AFP alone with further imaging confirming the diagnosis. Both of these were unsuitable for curative treatment. Majority (44%) were picked up on surveillance USS demonstrating abnormality then confirmed with further imaging. Fifty-six percent of patients with HCC underwent attempted curative treatment (liver transplantation 28%, resection 6% and radiofrequency ablation 22%); 23% received controlling treatment (TACE 6%, ethanol injection 17%) and 22% were referred for palliation. Conclusion: Our results show that a large proportion of HCC were detected in high risk group and 56% of these patients underwent curative treatment for HCC. A significant proportion (23%) also underwent other definitive treatment. There was a significant burden of HCC in the group conventionally classified as low risk group for HCC (18% of total HCC we identified in our series). 22% of our total identified HCC cases were not suitable for treatment other than palliation despite being on recommended surveillance and this may be improved by modifying surveillance interval or better definition of the high risk group. With this study we recommend present surveillance guidelines to be followed in all patients with cirrhosis, however, there may be scope for further improvement in outcome for cirrhosis patients developing HCC by modification of surveillance protocol in selected patients and also by modification of risk groups.